Effect of thyme and oregano essential oils on the shelf life of salmon and seaweed burgers. (July 2018) - Dolea, D; Rizo, A; Fuentes, A; Barat, JM; Fernández-Segovia, I
The effect of different essential oils on the quality and shelf life of fish and seaweed burgers during storage was evaluated. For this purpose, thyme and oregano essential oils were selected at a concentration of 0.05% (v/w). Three types of salmon and seaweed burgers were prepared: without essential oil, burgers with red thyme essential oil (0.05% (v/w)) and burgers with oregano essential oil (0.05% (v/w)), which were vacuum packaged and stored at 4 ℃ for 17 days. Physicochemical and microbiological analyses were carried out periodically throughout storage. The addition of both essential oils did not have any effect on the evolution of the pH, the moisture content or texture parameters. Only the thyme essential oil managed to slightly slow down the increase of total volatile basic nitrogen and trimethylamine nitrogen. The samples with oregano essential oil and especially those with thyme essential oil showed minor oxidation. The salmon and seaweed burgers without essential oils and those which contained oregano essential oil showed a faster increase of mesophilic counts than those which had thyme essential oil, but no noticeable improvement was observed in the shelf life of the burgers with thyme essential oil. To improve the shelf life of the fish and seaweed burgers, it would be necessary to increase the concentration of both essential oils.